(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
Professionalization and professionalism are based on systematic theoretical pillars and considered as more than necessary because their function is to provide the necessary work quality. The primary concept in this paper is aimed at professionalism and profession which creates and nourishes a distinctive, special culture, acquired with the socialization process. Hence, the theoretic explication of the paper is focused in the first place toward the scope of the professionalization concept, and subsequently toward perceiving the professionalism and profession, the competence and authority, accepted by the clients of a certain profession.